Anemia among Women Who Visit Bost Hospital for Delivery in Helmand Province, Afghanistan - Zabihullah Anwary; Muhammad Haroon Stanikzai; Wali Mohammad Wyar; Abdul Wahed Wasiq; Khushhal Farooqi (Anemia)
Background. Anemia is a global public health problem that affects a large number of pregnant women worldwide. In developed and developing countries, the number of pregnant women who become anemic ranges between 18% and 56%, respectively. The aim of this study was to determine the prevalence of anemia and factors associated with anemia among pregnant women who visit Bost Hospital for delivery in Helmand province, Afghanistan. Methods. This was a hospital-based cross-sectional study that included 787 pregnant women who visited Bost Hospital for delivery services from January to June 2019. Data was collected in a self-structured questionnaire, which included sociodemographic, obstetrics, and laboratory information. Data was analyzed using SPSS 21.00 Statistical software. The prevalence of anemia was presented as a percentage. Bivariate analysis and binary logistic regression were used to identify the predictors of anemia among pregnant women. Results. The overall prevalence of anemia in this study was 51% (95% CI = 48.7%–54.7%). The mean hemoglobin concentration among the study participants was 10.8 (±1.8) g/dL. On bivariate analysis, age group 30 years and above, rural residency and unemployment/housewives, multiparity, and no previous use of contraceptive were found to be associated with anemia. Binary logistic regression showed that multiparity (AOR = 3.09, 95% CI = 1.81–5.29) and no contraceptive use (AOR = 1.53, 95% CI = 1.08–2.16) were the independent predictors of increased anemia among pregnant women. Conclusion. Anemia was found to be a severe public health problem in the study area. Policymakers in Afghanistan must accelerate interventions to promote family planning. The need for prospective studies is also suggested to identify other factors associated with anemia among pregnant women.